EMBEDDED SENSOR NETWORK - S, Kavitha (Journal of ISMAC, 2023)
Sensors are quite important in the current world. Sensors advance society in a number of areas, including the monitoring of environment as well as human health, safety, and security. Advanced military, agricultural, medical, and disaster management areas frequently employ sensor nodes to streamline monitoring by humans. Due to the fact that sensors are frequently utilised in non-human environments and for monitoring purposes of terrestrial areas, a computer hardware and software combination known as an embedded system is created for this purpose. An embedded sensor network is a network that is positioned in the real world and communicates with it. The significance of embedded sensors in a network and how they operate are covered in this research.